Some Topological and Polynomial Indices (Hosoya and Schultz) for the Intersection Graph of the Subgroup ofã€– Zã€—_(r^n ) - Nawaf, Alaa J.; Mohammad, Akram S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Let be any group with identity element (e) . A subgroup intersection graph of a subset is the Graph with V ( ) = - e and two separate peaks c and d contiguous for c and d if and only if , Where is a Periodic subset of resulting from . We find some topological indicators in this paper and Multi-border (Hosoya and Schultz) of , where , is aprime number.